عقد التدريب الرياضي في التشريع اللجزائري - عباسة, طاهر; بافضل, محمد (Journal of Sport Science Technology and Physical Activities, 2018)
To prepare sportsman for competitions, it is necessary to use the services of coaches, whether in individual or collective sports. From this point of view, it is necessary to seek the legal qualification of the contract which binds these trainers to the club, as well as the obligations resulting from this type of contract in the Algerian legislation.